Action Research on Discourse Analysis of ESL Foundation Year Students: A Case of L1 Arabic-speaking Students - Amrendra Kumar Singh (Indonesian TESOL Journal, 2023)
This essay aims to present a brief qualitative account of authentic writing samples of Arabic-speaking ESL learners, looking at various cohesive discourse devices used, and at what are the elements that make them differ in their world views. The focus of this essay is written discourse, especially the use of connectors in short medical report writing exercises; brief excerpts have been taken from submissions by students currently pursuing undergraduate degrees at a Saudi university. Writing samples from short paragraphs of free writing have been analysed to understand the nature of language perception and the way English is learnt by the students. The implications of the study throw light on pedagogical practices as well as on learners’ needs. Discussion of this paper has implications for prevalent teaching practices and for areas of improvement in the students’ writing skill.     Keywords: Discourse analysis; L1 Arabic speaking; ESL; writing skill; foundation year